Determinants of social media marketing towards start-ups business - 'Aliah Syafina, Abd Rashid (2023)
Digital marketing is a way for businesses to communicate with people using the internet. It involves using different online tools like social media, blogs, and videos to promote products and services. As the internet becomes more popular, marketing strategies need to change to keep up with how people use technology. This research paper talks about how digital marketing is growing and how businesses can use it to be successful. It also talks about the good and bad things about using technology for marketing and suggests ideas for future research. The study will be divided into five chapter. In the first chapter, we will explain what the study is about and why it is important. We will also talk about what we aim to find out and how we plan to answer and the entire scope of the research. In the next chapter, we will cover the literature review which will provide other people's writing on social media marketing. This will help us learn more about how it has grown and why our study is important. We will use information from other studies to see the social media marketing towards start-ups. The third chapter tells us how the information was collected to make the research better. It explains how the choices made from sampling method to the population chosen to get more information. The context of methodology will give us lots of details about how the information was gathered and used to make the research better. In the fourth chapter which is findings part, we will show and explain all the important calculation we did based on the survey. After that, on the last chapter we will finish the paper by giving a conclusion. The conclusion will talk about what the results mean and suggest things to do in the future. We will also talk about the things we couldn't do because of limitations.